Analysis of Physical Properties and Evaluation of Heavy Element Concentrations in Euphrates River’s Fish in Nasiriyah City - Faisal, Ahlam; Maktoof , Afrah (University of Thi-Qar Journal of Science, 2025)
Environmental pollution is one of the most prominent problems that facing the world at the present time. The current study was conducted on the Euphrates River in the center of Nasiriyah city during the period time from September 2023 to Marsh 2024. Three locations were used in this study. The length of the river and some physical and chemical parameters of the water were studied. The temperature of the water and air was measured, in addition to the distribution of four heavy metals in fish. The current results were showed that the air temperature increased significantly in the third water position, and decreased significantly in the other water position, the water temperature increased significantly in the first water position, while decreased significantly in the other water positions. In contrast, the level of Neutrophil increased significantly in the second water position and decreased in the first water position at p. value < 0.05. The current results were showed a significant increase in the level of both Cd and Pb in muscle compared with gills, while the level of both Zn and Cu decreased significantly in muscle compared with gills. The study also recorded a significant difference at p. value < 0.05 in the level of trace elements between muscles and gills of fish during summer. The current results showed a significant increase in the level of all involved trace elements (Cd, Pb, Zn and Cu) in gills of fish comparing with muscles of fish during winter